Novel politics : democratic imaginations in nineteenth-century fiction - Armstrong, Isobel (Oxford University Press, 2016)
"Novel Politics' aims to change the current consensus of thinking about the nineteenth-century novel. This assumes that the novel is structured by bourgeois ideology and morality, so that its default position is conservative and hegemonic. Such critique comes alike from Marxists, readers of nineteenth-century liberalism, and critics making claims for the working-class novel, and systematically under-reads democratic imaginations and social questioning in novels of the period. To undo such readings means evolving a new praxis of critical writing. Rather than addressing the explicitly political and deeply limited accounts of the machinery of franchise and ballot in texts, it is important to create a poetics of the novel that opens up its radical aspects."--Jacket